2012
DOI: 10.1115/1.4006206
|View full text |Cite
|
Sign up to set email alerts
|

Critical Heat Flux in Submerged Jet Impingement Boiling of Water Under Subatmospheric Conditions

Abstract: Critical heat flux (CHF) characteristics in submerged jet impingement boiling of water on a heated copper surface are investigated at subatmospheric conditions. Data are reported at a fixed surface-to-nozzle diameter ratio of 23.8 and a fixed surface-to-nozzle height of 6 nozzle diameters. Three subatmospheric pressures of 0.176 bars, 0.276 bars, and 0.477 bars are considered, corresponding to fluid saturation temperatures of 57.3 °C, 67.2 °C, and 80.2 °C and liquid-to-vapor density ratios of 8502, 5544, and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Experiments by Cardenas and Narayanan [14][15][16][17][18]. Details on the experimental facility and experiments for jet impingement boiling using subatmospheric water and FC-72 are provided else where [18].…”
Section: Review Of Data Used In Correlationmentioning
confidence: 99%
See 4 more Smart Citations
“…Experiments by Cardenas and Narayanan [14][15][16][17][18]. Details on the experimental facility and experiments for jet impingement boiling using subatmospheric water and FC-72 are provided else where [18].…”
Section: Review Of Data Used In Correlationmentioning
confidence: 99%
“…To develop the jet impingement CHF correlation, the number of jet impingement CHF data points considered from the studies by Cardenas and Narayanan [14][15][16][17][18] is 46 (excluding pool boiling cases). Table 4 presents uncertainty estimates for measured and determined variables [23], Data reproducibility was studied by performing repetitions and replications of experiments and it was found that CHF varied between 4% and 6% [18].…”
Section: Review Of Data Used In Correlationmentioning
confidence: 99%
See 3 more Smart Citations